What predicts word reading in Arabic? - Hassanein, Elsayed E. A.; Johnson, Evelyn S.; Ibrahim, Sayed; Alshaboul, Yousef (Frontiers in Psychology, 2023)
Efficient and accurate word reading ability is critical for later reading success. As such, it is important to understand the component skills that underlie strong word reading ability. Although a growing research base points to the importance of phonological processing, morphological processing and orthographic processing for accurate and fluent word reading in Arabic, there are few studies that examine all three areas at one time to better understand their role in word reading. Additionally, it remains unclear whether the contribution of the various processes might differ across the early years when children are learning to read. 1,098 pupils in grades 1–3 participated in this study and took tests for phonological processing, morphological processing, orthographic processing, and word reading accuracy and fluency. According to the findings of regression analyses, the relative contribution of these underlying processes differed according to the method used to test word reading and the student’s grade level. Regarding accuracy, several subscales of phonological processing and two measures of orthographic processing accounted for significant differences in word reading accuracy for first graders. For second grade students, nonword repetition, elision, and all three measures of orthographic processing accounted for variance. In third grade, elision and memory for digits, word creation and morpheme identification, and letter/sound identification and orthographic fluency were significant predictors of word reading accuracy. In terms of fluency, two subscales of phonological processing, two measures of orthographic processing, and two measures of morphological processing explained significant differences in word reading fluency for first graders. For second grade students, nonword repetition, elision, RAN-digits, isolation, segmenting and all the measures of orthographic processing and word creation explained unique variance in word reading fluency. In third grade, elision, RAN-letters, RAN-digits and phoneme isolation, all measures of orthographic processing and morphological processing, explained variance in word reading fluency. Implications and future directions in research are discussed.